COMPARISON OF THE PAIN RELIEF EFFECT IN PAIN RELIEF IN AND AFTER HAND SURGERY IN CHILDREN OF AXILLARY LINE BRAINSYNCING WITH DIFFERENT CONCENTRATIONS OF LEVOBUPIVACAINE (Vietnam Journal of Community Medicine, 2026)
Objective: To compare the efficacy of pain reduction during and after forearm and hand surgery in children using ultrasound-guided axillary brachial plexus block with Levobupivacaine 0.2% versus Levobupivacaine 0.25%.Subjects and methods: This study was conducted on 60 patients (aged 3-16 years) receiving axillary brachial plexus block at the Department of Anesthesiology and Intensive Care, National Children’s Hospital. Patients were randomly assigned to 2 groups: group 0.2 which used Levobupivacaine 0,2%, and group 0.25 which used Levobupivacaine 0,25%. Both groups used a volume of 0.5 ml/kg, maximum 20 ml.Results: The two groups were comparable regarding general characteristics: mean age 7.25 ± 3.34 years; weight 26.71 ± 10.39 kg; height 120.07 ± 17.93 cm; surgical duration 61.45 ± 22.19 minutes (p > 0.05). The efficacy of intraoperative anesthesia was good in both groups (100%). The duration of sensory and motor block for group 0.2 was 255.17 ± 43.10 minutes and 214.40 ± 38.46 minutes, respectively, and for group 0.25 was 356.97 ± 46.35 minutes and 311.53 ± 43.94 minutes (p < 0.001). The duration of analgesia for group 0.2 and group 0.25 was 367.87 ± 44.25 minutes and 414.30 ± 50.01 minutes, respectively (p < 0.05). The number of times additional analgesics were administered within 24 hours post-surgery was comparable between the two groups (p > 0.05). 2/60 cases reported pain at the injection site, 1/60 cases reported nausea. No excessive sedation or severe adverse effects were recorded.Conclusion: Both groups achieved good intraoperative anesthetic efficacy. Group 0.2 had an earlier recovery time for sensory and motor function (p < 0.001), and a shorter postoperative analgesia time (approximately 47 minutes less on average) compared to group 0.25 (p < 0.05). There was no difference in the number of times rescue analgesics were administered between the two groups over 24 hours after surgery (p > 0.05).
Keywords: Brachial plexus block, regional anesthesia, axillary approach, children, drug concentration, pain management.